ECONOMIC DEVELOPMENT OF LIGHT INDUSTRY IN KAZAKHSTAN AND RUSSIA IN THE CONDITIONS OF THE EAEU - T.G. Toilybek (Academic Journal of Physical and Chemical Sciences, 2019)
The economic development of light industry in Kazakhstan and Russia under the conditions of the EAEU operates according to the general rules of the game, which are established by the participants of the Eurasian Economic Union. Since only by protecting the domestic market of Kazakhstan from poor-quality imports, it will be possible to reanimate the domestic light industry. However, our entrepreneurs are not particularly interested in working in this sector of light industry because of long-term investments. Today, in Kazakhstan, production facilities have been modernized and have the ability to produce high quality products. That is, it complies with the necessary requirements of generally accepted international standards, which will provide an opportunity for trading in foreign markets. According to the author, the dynamics of the development of light industry with this state support will allow an increase in the competitiveness of products and the development of the industry as a whole.